The demon of geopolitics how Karl Haushofer "educated" Hitler and Hess - Herwig, Holger H. 1941- (Rowman & Littlefield, 2016)
"Herwig explores the life and times of Karl Haushofer, widely recognized as the 'father of geopolitics' and the architect of Lebensraum, the rationale for Germany's control of Europe and the world"--Provided by publisher